Socio-ethical implications of using AI in accelerating SDG3 in Least Developed Countries - Kutoma Wakunuma; Tilimbe Jiya; Suleiman Aliyu (Journal of Responsible Technology, 2020)
Artificial Intelligence (AI) is playing a crucial role in advancing efforts towards sustainable development across the globe. AI has the potential to help address some of the biggest challenges that society faces including health and well-being. Thus, AI can be useful in addressing some health and well-being related challenges by accelerating the attainment of the UN's Sustainable Development Goal 3 (SDG3), namely Good health and well-being. This paper draws on the Organisation for Economic Co-operation and Development (OECD) Development Assistance Committee (DAC) list of Official Development Assistance (ODA) and the Price Waterhouse Coopers (PwC) SDG selector to identify the SDG that is prioritised in Least Developed Countries (LDCs). Out of 32 least developed African countries on the list, SDG3 was the most common SDG, suggesting that health and well-being is a priority for these countries. In order to understand the opportunities and challenges that might result in applying AI in the acceleration of SDG3, the paper uses a SWOT analysis to highlight some socio-ethical implications of using AI in advancing SDGS in the identified LDCs on the DAC list.